Comparative Efficacy of Quadratus Lumborum Muscle Energy Technique with Gluteus Medius Strengthening Versus Gluteus Medius Strengthening Alone in Sacroiliac Joint Dysfunction: A Randomized Controlled Trial - Rabail Rani Soomro; Hossein Karimi; Syed Amir Gilani (Diagnostics)
Background: Pain in the sacroiliac joint is the most prevalent and often overlooked. The sacroiliac joints are thought to be sources of pain in roughly 10% to 25% of patients with chronic lower back pain. Due to the biomechanical nature of the joint, muscle imbalance is the most important cause of sacroiliac joint dysfunction. The hamstring and gluteus medius are the primary muscles involved in postural dysfunction-related muscle imbalance; however, the quadratus lumborum’s role in the compensatory mechanism is becoming more apparent, and its potential for treatment in conjunction with gluteus medius strengthening has not yet been investigated. Gluteus medius exercises, along with conventional treatment, are routinely given to patients with sacroiliac joint dysfunction; however, the aim of this study is to explore the additional effects of the muscle energy technique (MET) on the quadratus lumborum along with strengthening of the gluteus medius on pain, disability and quality of life of patients with sacroiliac joint dysfunction. Methods: Using a computer-generated random number table, seventy patients with unilateral sacroiliac joint pain were divided equally and randomly into two groups. Prior to initiating treatment, baseline measurements were taken using a hand-held dynamometer, visual analog scale (VAS), Oswestry Disability Index (ODI-U) and short form 36-item survey (SF-36v2) to assess strength, pain, functional disability and quality of life, respectively. Over the course of four weeks, all patients received twelve sessions, and both the pre- and post-intervention outcome measures were documented. Results: After 4 weeks of treatment, both groups showed statistically significant (p < 0.005) mean improvements in muscle strength, pain, disability and quality of life before and after intervention. However, the mean improvements in post-intervention on a dynamometer, VAS, ODI and SF-36 were better in the MET with exercise group (METGME) as compared to the conventional group with exercise (CTGME), with a larger effect size. Conclusions: The muscle energy technique, applied to the quadratus lumborum in combination with gluteus medius strengthening, is more effective clinically and significantly in improving pain, disability and quality of life in comparison to conventional treatment of sacroiliac joints with gluteus medius exercises.